Formant Characteristics of Malay Vowels of Perlis, Kelantan and Terengganu - Jamil, Nursuriati; Ramli, Izzad; Ardi, Norizah (Universiti Utara Malaysia Press, 2019)
The pronunciation of Malay vowels are taught according to the International Phonetic Association transcription sound chart. The documentation for pronunciations are conducted by describing and distinguishing the vowels sound through impressionistic. In the last five years, several studies were carried out to quantify the standard Malay vowels pronunciation using formant frequencies. However, only one work was identified that measures Malay vowels using formant frequencies for the Kedah district. Nonetheless, there were contradiction in some of the findings as the spoken vowels were extracted from a read speech, that may not be representative of the natural dialect. Therefore, this paper investigated the Malay vowels variations from three districts (Perlis, Kelantan, and Terengganu) using spontaneous speeches acquired in a natural setting. Eight (8) Malay vowels were collected from local males and females residing in Perlis, Kelantan, and Terengganu. Four formant frequencies (F1-F4) were measured from the vowels extracted from the spontaneous speeches of the locals. Further analysis on the first and second formant suggest that the Malay vowels of Terengganu and Kelantan have a broader range of formants that are located in approximately the same position in the mouth. However, the vowels of the Perlis dialects were closely positioned in a narrower region of the mouth. A Malay vowel diagram was plotted that can be used for future reference in research and as an educational tool for language learning. Furthermore, Kelantan and Terengganu dialects are shown to be similar based on the first and second formants.